Open innovation change agents in large firms: how open innovation is enacted in paradoxical settings. (1st October 2019) - Remneland Wikhamn, Björn
Abstract : This paper theorizes how change agents in large firms enact open innovation with small firms. The open innovation change agent is highlighted as a key internal actor for the transformational work needed to put open innovation into practice. The paper presents an empirically grounded theoretical model of how these actors work, emphasizing the two activities of 'anchoring' and 'navigating', with the purpose of bridging the inside and outside of the corporation. In applying a paradox perspective on open innovation enactment, it is explained how these change agents act as both catalysts and guards for collaboration, continuously balancing different paradoxical demands. Theoretical and managerial implications in relation to these findings are discussed.